2003
DOI: 10.1159/000070803
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Outcome of Fetal Echogenic Bowel

Abstract: Objective: To assess the frequency of certain etiologies in fetal echogenic bowel and the related pregnancy outcome. Study Design: A retrospective study including 215 cases. Ultrasound findings included bowel abnormality, malformations, growth retardation and Doppler abnormalities. Amniocentesis was performed in 196 cases to screen for abnormalities in karyotype, cystic fibrosis gene and infection. The color of amniotic fluid and a history of first-trimester bleeding were also noted. Outcome according to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This disease is now a well‐known example of a pathology that can be diagnosed before birth following ultrasonographic (US) detection of suggestive signs. In recent years, fetal echogenic bowel (FEB) has been clearly associated with the in utero diagnosis of CF . The situation is less clear for other US signs that have inconsistently been reported to be associated with CF.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is now a well‐known example of a pathology that can be diagnosed before birth following ultrasonographic (US) detection of suggestive signs. In recent years, fetal echogenic bowel (FEB) has been clearly associated with the in utero diagnosis of CF . The situation is less clear for other US signs that have inconsistently been reported to be associated with CF.…”
Section: Introductionmentioning
confidence: 99%
“…43 In addition to abnormal chromosome numbers and structure, chromosomal microdeletions or microduplications may contribute to the pathogenesis of fetal echogenic bowel. 3 Our data showed that both karyotyping and CMA are effective to detect chromosomal aneuploidy; however, CMA may identify the origin, fragment size and pathogenicity of the supernumerary marker chromosome, which facilitates the precision evaluation of the prognosis in fetuses with echogenic bowel during the genetic counseling. 11 Previous studies have shown that CNV, a risk factor for complicated developmental malformations, 44,45 is a major contributor to fetal echogenic bowel.…”
Section: Discussionmentioning
confidence: 80%
“…2 The majority of FEB is considered as non-specific ultrasound features, which may attribute to intestinal hypoperistalsis. 3 However, this disorder is also reported to be linked with an increased risk of chromosomal abnormality, intrauterine infections, cystic fibrosis, congenital bowel abnormality, intrauterine growth restriction, and fetal mortality. 4 In addition, the clinical significance of FEB is reported to vary in the echogenic intensity, 5 and higher echogenic intensity predicts poorer pregnant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Echogenic bowel is a sonographic soft marker which is associated with a favourable outcome in majority of cases [7]. However, in up to 3% fetuses it is representative of a gut malformation, which may become evident antenatally at later gestation as dilated bowel or may be a postnatal diagnosis [8]. Hirschsprung disease has been reported to present with echogenic bowel in antenatal period in 2/22 cases in one retrospective study [9].…”
Section: Discussionmentioning
confidence: 99%